Development of Arenal android application: a supplementary tool in learning the human urinary system - Mohamad Zainal, NH; Naim, MH; Mohd Nor, NH; Mohd Thani, S; Rahmat, RWOK (Penerbit Universiti Sains Malaysia, 2024)
Augmented reality (AR) is an interactive three-dimensional (3D) experience that uses computers to overlay virtual information in the real world. We aimed to develop an online 3D AR of human urinary system (HUS) as a supplementary tool to aid in the teaching and learning process whether via online or traditional teaching methods, particularly for undergraduate medical students. Augmented reality human urinary system (ARenal) is an Android application that implements AR for better comprehension of the HUS. It is an original work of 3D models, diagrams, pictures, notes, self-recording videos, quizzes and a manual. The AR elements will improve learning effectiveness and attention span, enabling students to comprehend anatomical principles, basic physiology, and common disorders of HUS. Instead of 3D on paper, students can access educational resources and AR tools via a detailed 3D kidney model on Android devices. The user acceptability testing (UAT) (n = 10) revealed that 60% of participants indicated it was their first experience with AR, and 60% strongly agreed that ARenal was operating well. They also strongly agreed that it is user-friendly (50%). Most participants expressed a higher level of acceptability for ARenal and recommended adding more activities, games, quizzes, and other features to the 3D model for better interaction. In conclusion, ARenal has the potential to be employed as an additional aid for learning the HUS.